2002
DOI: 10.1046/j.1365-2311.2002.0372a.x
|View full text |Cite
|
Sign up to set email alerts
|

Mating behaviour and light conditions cause seasonal changes in the dispersal pattern of the satyrine butterfly Lethe diana

Abstract: Summary1. The spatial arrangement of resources and climatically favourable sites affects the dispersal pattern of butterflies.2. The microdistribution of the satyrine butterfly Lethe diana changes seasonally, meaning that the relative spatial arrangement of resources also changes seasonally. The seasonal change in the dispersal pattern of this butterfly was studied.3. Males of the May–June generation tended to stay in a restricted habitat patch while females of the same generation did not. A number of the May–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Ide, unpublished data). To separate the two generations, census data were divided into two groups, that is, from July to August and from September to October (Ide 2000a(Ide , 2002. In this way, three generations can be distinguished: the May-June, July-August, and September-October generations.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Ide, unpublished data). To separate the two generations, census data were divided into two groups, that is, from July to August and from September to October (Ide 2000a(Ide , 2002. In this way, three generations can be distinguished: the May-June, July-August, and September-October generations.…”
Section: Study Sitementioning
confidence: 99%
“…Males of the satyrine butterfly Lethe diana (Butler) hold territories around sunlit branch tips that face an open space in the afternoon (Fukuda et al 1984;Ide 2002). L. diana has three generations a year, and territorial behaviour is observed in the generations in May-June and in September-October, but not in July-August (Ide 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bamboo grass S. veitchii var. hirsuta, the main food plant of T. varia in this area, occurs in scattered clumps on the forest floor (Ide 2002). For this study, the blades of this plant were classified into two age classes: current year or overwintered.…”
Section: Field Investigationmentioning
confidence: 99%
“…A speciWc example of this can be found in the limited literature on butterXy edge responses. Studies have shown that certain butterXy species either avoid (Schultz 1998;Haddad and Baum 1999) or are attracted (Ravenscroft 1994;Bergman 1999;Wahlberg 2001;Ide 2002) to certain edges. Although some of these studies include data showing how changes in microclimate or host plant distribution were associated with these patterns, there is no overarching framework to explain when speciWc butterXy species should be expected to avoid, be attracted to, or ignore speciWc edge types.…”
Section: Introductionmentioning
confidence: 99%